PROPHETICAL DIMENSION IN KHOTBAH DI ATAS BUKIT NOVEL BY KUNTOWIJOYO - El Farouq Ghazali, Muhammad Ayyinna Yusron; Machmudah, Umi (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2019)
This literature study aims to explain the prophetical dimension in Khotbah di Atas Bukit novel by Kuntowijoyo. The results of the study found that there is a humanization dimension of the Khotbah di Atas Bukit novel which includes strengthening in assertiveness, a sense of social solidarity, and personality. The dimensions of the liberation of novels on the Khotbah di Atas Bukit novel found include the activity of freeing oneself from worldliness, liberation from the social inequality. In the novel dimensions of transcendence the Khotbah di Atas Bukit novel was found to be akidah, khauf, tawakal, raja'. This dimension of humanization, liberation and transcendence represents the ethica prophetic component of prophethood underlying the creation of the Khotbah di Atas Bukit novel.